What Drives Inflation in the Major OECD Economies? - Moccero, Diego (OECD Publishing, 2011)
This paper presents an empirical analysis of the determinants of inflation in the United States, Japan, the euro area and the United Kingdom, focusing on the role of resource utilisation, inflation expectations, inflation persistence and imported inflation. It also includes a cross-sectional analysis that focuses on inflation dynamics over episodes of persistent large slack and low inflation. The main findings of this analysis are as follows: i) During the crisis, the stability of inflation expectations has held up actual inflation, so far preventing the huge slack in resource utilisation from leading to a disinflationary spiral; ii) Disinflationary pressures also seem to have been moderated by the flattening of the Phillips curve in an environment of persistent large economic slack and low inflation; iii) The link between long-term inflation expectations and past inflation outcomes has become weaker over time and appears to have almost disappeared recently; iv) The estimated Phillips curves coupled with the November 2010 projection of explanatory variables presented in the OECD Economic Outlook No. 88 and excluding the recent period of strong commodity prices point to inflation remaining low but positive, except in Japan where deflation is expected to continue past end-2012; v) The inflation outlook and associated risks argue for withdrawing monetary policy accommodation gradually in the short term, while being vigilant about the build up of broad-based inflationary pressures over the medium term
Keywords: Economics